Palmar lichen nitidus following Blaschko lines with nail involvement in a child. - Boccaletti, V.; Salsi, B.; Ricci, R.; De Panfilis, G. (European Journal of Pediatric Dermatology, 2007)
Lichen nitidus (LN) is a chronic dermatosis characterized by uniform papules varying in color from skin, yellow, brown, red or blue depending on the background color of the patient skin. The upper extremities, trunk and glans penis are the most common sites of involvement. We report the case of a 6-year-old boy with a rare palmar and nail involvement following Blaschko lines, reminding of a lichen striatus, who showed to be affected by LN. Therapy resulted only in temporary and partial improvement of the lesions. To our knowledge this is the first report of LN following Blaschko lines.